Energy-efficient modified LEACH protocol for Wireless Sensor Networks (WSN) - Kumar, Vivek; Malhotra, Ruchika; Ansari, M. Yousuf (International Journal of Scientific Research in Computer Science and Engineering, 2024)
Numerous researches have been done for minimization of the consumption of energy on wireless sensor networks (WSNs). The reason behind such research is because of a large number of applications in this field. We have proposed a method for the same in our paper. We have implemented various approaches to minimize the energy consumption and based on various results which are calculation of cluster count, Communication between the packets and lifetime matrices which are number of alive and dead nodes. The techniques implemented in the system are simple leach, I-leach, modified I-Leach and the Multi-Hop Clustering Routing method in Leach. On comparing all the techniques, it is found how the suggested technique performs which is Multi-Hop Clustering Routing is better in network lifetime as well as in terms of stability period.